2022-RA-1346-ESGO Predictive factors for adnexal involvement in Endometrial Cancer, with a focus on FIGO Stage IIIA, an uncommon entity. (20th October 2022) - Dinoi, Giorgia; Fera, Eleonora La; Restaino, Stefano; Pafundi, Pia Clara; Gioè, Alessandro; Naccarato, Laura; Palmieri, Emilia; Scambia, Giovanni; Fanfani, Francesco
Abstract : Introduction/Background: To assess the incidence of endometrial cancer (EC) FIGO stage IIIA, and evaluate predictors of adnexal involvement, and its role as prognostic factor of recurrence and death in EC. Methodology: Records of all consecutive EC patients who underwent primary surgery between January 2005 and November 2021 at Fondazione Policlinico A. Gemelli, Rome, were retrospectively reviewed. Potential predictive factors of adnexal involvement were assessed by logistic regression models. Overall survival (OS) and recurrence-free survival (RFS) were estimated using Kaplan-Meier method and potential independent prognostic factors assessed by Cox proportional-hazard models. Results: 2079 patients were finally included in the study. Of those, 55 were stage IIIA EC (annual incidence 0.11%). Recurrences occurred in 16 out of 55 patients (29.1%), mostly pelvic and lymphatic (43.8% each). Notably, 27/39 (69.2%) who did not recur underwent chemotherapy with external beam radiation therapy. 5-years RFS and OS in stage IIIA were 72.7% and 85.5%, respectively.Overall, 207 patients had adnexal involvement (annual incidence 0.42%), with myometrial infiltration [(MI) OR 1.51, 95% 1.03–2.21; 0.035], isolated and diffuse lymphovascular space invasion [(LVSI) OR 2.51, 95%CI 1.59–3.97; OR 3.27, 95%CI 2.16–4.94; p<0.001, respectively), cervical stromal invasion [(CSI) OR 4.26, 95%CI 3.00–6.05; p<0.001], and instable mismatch repair (iMMR) phenotype (OR 1.96, 95%CI 1.24–3.08; p=0.004) found as independent predictors (Table). Remarkably, adnexal involvement in EC further revealed an independent negative predictive factor of RFS (HR 3.20, 95%CI 1.66–6.18; p=0.001), whilst only a suggestive negative role emerged on OS (HR 1.73, 95%CI 0.93–3.24; p=0.086). Consistently, 5-years RFS and OS were shorter among women with adnexal involvement compared with those without (63.3 vs. 87.5%, and 68.6 vs. 92.9%, p<0.001, respectively). Conclusion: Main predictors of adnexal involvement in EC are iMMR phenotype, MI, isolated and diffuse LVSI, and CSI. Although adnexal involvement incidence is low, this may be associated with higher recurrence risk.